The Impact of Political Competition on Economic Growth: Evidence from Municipalities in South Africa. (26th November 2018) - Obikili, Nonso
Abstract: This paper examines the impact of political competition on economic growth. In this paper, I show that internal political dynamics, distinct from the type of political system, can having different effects on growth. Using results from the 1994 and 1999 elections in South Africa, I show that municipalities with higher levels of political competition have shown lower levels of economic growth. I use individual level surveys to show that this political competition is associated with political paralysis, dissatisfaction with the current democracy and government and lower optimism about the future.